In-depth characterization of the raw material corn steep liquor and its bioavailability in bioprocesses of Penicillium chrysogenum. (July 2018) - Hofer, Alexandra; Hauer, Stefan; Kroll, Paul; Fricke, Jens; Herwig, Christoph
Graphical abstract: Highlights: In-depth characterization of liquid and solid phase of corn steep liquor. Evaluation of bioavailability of amino acids in corn steep liquor. Introduction of solubilization and enzymatic release kinetics. Demonstration of the impact of release kinetics on process interpretation. Abstract: Although corn steep liquor (CSL) is a commonly applied raw material in biopharmaceutical production processes, its mechanistic impact on process performance is still not completely unraveled. It is a multicomponent and multiphase matrix, including free and bound ingredients. Hence, changes in bioavailability during cultivations and their effect on the process are challenging to determine. In this study we want to give a holistic overview of CSL considering both phases as well as free and bound ingredients. With the example of amino acids bioavailability in CSL was assessed with respect to i) initial bioavailability ii) solubilization release in media and iii) enzymatic release by Penicillium chrysogenum during a fermentation process. Ten amino acids showed an enzymatic release including arginine, which is used for biomass formation, and valine, a precursor amino acid for penicillin production. Applicability of these results was demonstrated on a penicillin process for both these amino acids showing opposed meaning of specific rates depending on inclusion of release kinetics. Overall, the detailed characterization of CSL with high analytical quality and the consideration of release kinetics resulted in a huge impact on the interpretation of the process with respect to fungal physiology and metabolism.